Functional conservation of MBD proteins: MeCP2 and Drosophila MBD proteins alter sleep. (6th September 2016) - Gupta, T.; Morgan, H. R.; Bailey, J. A.; Certel, S. J.
Abstract : Proteins containing a methyl‐CpG‐binding domain (MBD) bind 5mC and convert the methylation pattern information into appropriate functional cellular states. The correct readout of epigenetic marks is of particular importance in the nervous system where abnormal expression or compromised MBD protein function, can lead to disease and developmental disorders. Recent evidence indicates that the genome of Drosophila melanogaster is methylated and two MBD proteins, dMBD2/3 and dMBD‐R2, are present. Are Drosophila MBD proteins required for neuronal function, and as MBD‐containing proteins have diverged and evolved, does the MBD domain retain the molecular properties required for conserved cellular function across species? To address these questions, we expressed the human MBD‐containing protein, hMeCP2, in distinct amine neurons and quantified functional changes in sleep circuitry output using a high throughput assay in Drosophila . hMeCP2 expression resulted in phase‐specific sleep loss and sleep fragmentation with the hMeCP2‐mediated sleep deficits requiring an intact MBD domain. Reducing endogenous dMBD2/3 and dMBD‐R2 levels also generated sleep fragmentation, with an increase in sleep occurring upon dMBD‐R2 reduction. To examine if hMeCP2 and dMBD‐R2 are targeting common neuronal functions, we reduced dMBD‐R2 levels in combination with hMeCP2 expression and observed a complete rescue of sleep deficits. Furthermore, chromosomal binding experiments indicate MBD‐R2 and MeCP2 associate on shared genomic loci. Our results provide the first demonstration that Drosophila MBD‐containing family members are required for neuronal function and suggest that the MBD domain retains considerable functional conservation at the whole organism level across species. Abstract : Recent evidence indicates that the genome of Drosophila melanogaster is methylated and two methyl‐CpG‐binding domain (MBD) proteins, dMBD2/3 and dMBD‐R2, are present. Does the MBD domain retain the molecular properties required for conserved cellular function? Using the highly quantifiable sleep assay, we first determined that expressing human MeCP2 (hMeCP2) in octopamine neurons results in specific sleep deficits that were dependent on the MBD domain. Second, reducing the levels of dMBD‐R2 and dMBD2/3 generated the same sleep fragmentation defects and furthermore, the hMeCP2‐mediated sleep deficits were rescued through a concomitant reduction in the endogenous MBD proteins. Our results provide the first demonstration that Drosophila MBD proteins are required for neuron function and indicate conservation in the cell‐specific functions of epigenetic translators.